Kajian Faktor Budaya Organisasi Dalam Meningkatkan Prestasi Kerja: Satu Kajian di Pejabat Tanah Selangor - Mohd Sharif, Mohamad Yaakob (2011)
This study aims to investigate the relationship between organizational culture with a work performance at the Land Office in the state. This study was also conducted to determine whether the dimensions of organizational culture is in the response oriented factors, oriented rewards, support, communication and participation oriented affect work performance among the officers and land office staff. A total of 186 questionnaires were distributed, only 100 questionnaires collected can be used for analysis. Data analyzed using the "Statistical Package for Social Science" (SPSS) version 16.0. Thc study showed that the level of organizational culture among the officers and land office staff of the five dimensions of organizational culture is at a moderate level (satisfactory). The five dimensions of organizational culture studied has a significant positive relationship to job performance. However, the strength of the relationship is low (weak) for support and communication with job performance. While the other dimension is not influenced significantly on performance. So the management at the land office should focus on aspects of support and communication to improve work performance.